EFFECT OF LIQUIDITY RATIO AND SOLVENCY RATIO ON STOCK PRICES IN PT KALBE FARMA TBK - Lisdawati Lisdawati; Endang Nurita; Akhmad Akbar (International Journal of Economy, Education and Entrepreneurship, 2022)
This study is entitled “Effect of Liquidity Ratio and Solvency on Stock Prices in PT Kalbe Farma TBK." This study aims to determine whether or not there is an Effect of Liquidity Ratio and Solvency on stock prices, which PT Kalbe Farma Tbk owns. Liquidity, Solvency, and Stock Price are measured by looking at the company's financial statements. The statistical methods used in this research are descriptive statistical test, classical assumption test, multiple linear regression, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing performed with the T and F test at a significance of 5%. This study proves that Liquidity Ratio and Solvency simultaneously have an effect. In addition, this study also demonstrates that the partially Liquidity Ratio has a significant negative impact on stock prices, and the Solvency Ratio has a significant negative effect on stock prices